Imag(in)ing the Anthropocene: Nature Films and/as Creation Tales - Vivanco, Luis A. (Journal for the study of religion, nature and culture, 2019)
The popular association of nature films with scientific objectivity and secular environmentalism obscures how these films also deploy mythological, etiological, and cosmogonic symbols, themes, and narratives to create worlds that appeal to audiences. From Disney's Nature's Half Acre to March of the Penguins, nature films have employed technical artifice to show nature as it is', and at the same time operated as a means of storytelling about Creation as a sublime order suffused with meaning and purpose. But in these films, humans largely remained outside the natural' field of reference. At the threshold of the Anthropocene, in which concerns about human responsibility for degraded planetary conditions are highlighted, new films like Racing Extinction and the Earth—A New Wild series have explored the potential of creating alternative imaginary and visual worlds of nature that include humans, to support the generation of renewed moral purpose for addressing the global ecological crisis.